2019
DOI: 10.15386/cjmed-1101
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of Angiogenic Factors In Microvascular Angina

Abstract: Background. Recent studies have suggested that angiogenic factors may affect vascular endothelial integrity. On the other hand, endothelial dysfunction is the main pathological mechanism in microvascular angina (MVA) or cardiac syndrome X. Therefore, we aimed to determine the levels of angiogenic factors in MVA patients. In addition, we investigated the effects of metoprolol, as a beta blocker agent, on the serum levels of these factors.Methods. Thirty patients with MVA (17 female/13 male; mean age: 55.53±9.18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…39,40 Moreover, angiogenic factors have been investigated for their possible role in affecting endothelial function and integrity, leading to CMD and MVA. Asl et al 41 measured angiogenic factors levels in 30 MVA patients and 20 healthy controls; they found that the patients had significantly higher levels of Angp-2 and Tie-2 than controls. Afterward, patients with MVA underwent 4 weeks of metoprolol therapy, and at the end of this period, no significant changes were found in the levels of angiogenic factors compared with baseline values.…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…39,40 Moreover, angiogenic factors have been investigated for their possible role in affecting endothelial function and integrity, leading to CMD and MVA. Asl et al 41 measured angiogenic factors levels in 30 MVA patients and 20 healthy controls; they found that the patients had significantly higher levels of Angp-2 and Tie-2 than controls. Afterward, patients with MVA underwent 4 weeks of metoprolol therapy, and at the end of this period, no significant changes were found in the levels of angiogenic factors compared with baseline values.…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…Single studies have reported higher levels of serotonin, 75 stearic acid, 76 ornithine, 76 cardiac bridge integrator 1, 77 galactin‐3, 14 galectin‐4, 34 angiopoietin‐2 and tyrosine kinase‐2 receptor, 78 lymphocyte DNA damage, 79 NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide), 62 and red blood cell distribution width 62 in CMD compared with control subjects, and no difference in apolipoprotein‐C levels in CMD compared with controls. 31 In a study of 97 subjects with CMD, galectin‐4 levels correlated with myocardial blood flow reserve.…”
Section: Resultsmentioning
confidence: 99%